Where memories lie - Crombie, Deborah (Crombie, Deborah. Duncan Kincaid & Gemma James., 2008)
Detective Inspector Gemma James and her partner, Duncan Kincaid, must navigate the shadowy and secretive world of London's monied society to discover a jewelry piece's connection to a murderer and a pair of refugees from Nazi Germany.